Analisis Unjuk Kerja Improved Sinc Power Pulse pada Sistem OFDM Melalui Kanal Frequency Selective Fading - Prayoga, Kadek Agus Mahabojana Dwi; Wirastuti, NMAE Dewi; Pramaita, Nyoman (Majalah Ilmiah Teknologi Elektro; Vol 18 No 3 (2019): (September - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2019.v18i03.P04, 2019)
The combination OFDM (orthogonal frequency division multiplexing), and pulse shaping are expected to reduce the effects of Inter Carrier Interference (ICI) and error occurred. This study aimed to compare the performance of OFDM without pulse shaping nd OFDM with pulse shaping  Improved Sinc Power (ISP) pulse through Frequency Selective Fading channel, in terms of BER (bit error rate) vs. Eb/No (energy per bit to noise power spectral density ratio). This study implemented simulation using Matlab R2018a. The results of the simulation OFDM with ISP pulse system performance has better results than OFDM without pulse shaping. In the transmission Frequency Selective Fading channel, to reach 10 - 1 BER value in OFDM with ISP pulse was required Eb/No of 2 dB. While the OFDM without pulse shaping systems required Eb/No 10  dB. Keywords — OFDM, Pulse Shaping, ICI, ISP pulse, Frequency Selective Fading.